Electrical energy per order determination for the removal pollutant from industrial wastewater using UV/Fe 2+ /H 2 O 2 process: Optimization by response surface methodology - Asaithambi, P.; Alemayehu, E.; Sajjadi, B.; Abdul Raman, Abdul Aziz (Elsevier, 2017)
Comparison of UV, H2O2, Fe2+, UV/H2O2, UV/Fe2+, Fe2+/H2O2 and UV/Fe2+/H2O2 processes for the removal of percentage color, COD and electrical energy per order from the effluent distillery industry. The results showed that, UV/Fe2+/H2O2 process yield higher percentage color and COD removal with low electrical energy per order than UV, UV/H2O2, UV/Fe2+ process. To obtain the UV/Fe2+/H2O2 process performance by operating various parameters on the percentage color and COD removal using response surface methodology. A Regression quadratic model describing the percentage color and COD removal efficiency of UV/Fe2+/H2O2 process were developed and validate by analysis of variance. Experimental results showed that, UV/Fe2+/H2O2 process can effectively reduced 96.50% of color and 84.40% of COD removal of the distillery industry wastewater under the optimum conditions such as Fe2+-1.50 mM, H2O2-200 mM, COD-1500 ppm and pH-3.2, respectively. Result concluded that, UV/Fe2+/H2O2 process can be used effectively for the treatment of real industrial effluent.